Low-grade multicentric glioma: a rare entity - Vargas-Urbina, John (2024)
Multiple gliomas (multifocal and multicentric) are rare in low-grade gliomas. In multicentric gliomas, their etiology is poorly understood, and their management is controversial. A 27-year-old female patient, with two lesions compatible with low-grade glioma, confirmed by pathological study, for which; she received chemotherapy and radiotherapy, maintaining stable disease after one year of follow-up; she could not undergo surgery because the lesions were located in eloquent areas. For this type of patient, the standard of care is surgery whenever feasible based on eloquence and vascular involvement, followed by chemotherapy and radiotherapy like treatment given in single gliomas. Low-grade multicentric gliomas are a rare pathology that must be managed by a multidisciplinary team where surgery is the standard of care whenever feasible, followed by chemotherapy and radiotherapy.